2004
DOI: 10.1557/proc-841-r10.9/t6.9
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman Mapping and Analysis of Indentation-Induced Phase Transformations in Germanium

Abstract: Although it has been confirmed by diamond anvil cell experiments that germanium transforms under hydrostatic pressure from the normal diamond cubic phase (Ge-I) to the metallic β-tin phase (Ge-II) and re-transforms to Ge-III (ST12 structure) or Ge-IV (BC8 structure) during release of the pressure, there are still controversies about whether the same transformations occur during nanoindentation. Here, we present new evidence of indentation-induced phase transformations in germanium. Nanoindentation experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Using Raman mapping they showed that the extruded material 22 contained a-Ge, but there was also strong evidence for transformation of some of this phase to nanocrystalline dc-Ge. 32 Gogotsi and co-workers 12,21,23 and Oliver et al 30 also observed a-Ge around the residual indent area (extruded material) when phase transformation of dc-Ge took place under indentation. However, since the starting material was dc-Ge in all of these studies, from Raman spectra it was extremely difficult to distinguish the presence of (nanocrystalline) dc-Ge in the end phase from the starting dc-Ge phase.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Using Raman mapping they showed that the extruded material 22 contained a-Ge, but there was also strong evidence for transformation of some of this phase to nanocrystalline dc-Ge. 32 Gogotsi and co-workers 12,21,23 and Oliver et al 30 also observed a-Ge around the residual indent area (extruded material) when phase transformation of dc-Ge took place under indentation. However, since the starting material was dc-Ge in all of these studies, from Raman spectra it was extremely difficult to distinguish the presence of (nanocrystalline) dc-Ge in the end phase from the starting dc-Ge phase.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, sharp indenters, high loads and/or fast loading rates were observed to favor deformation by phase transformation. [20][21][22][23][24] When using sharp indenter tips, Jang et al 22,32 noted that extensive extrusion of material outside of the contact area always accompanied a phase transformation and they suggested that this observation in itself can be used to infer that a phase transformation had occurred. Using Raman mapping they showed that the extruded material 22 contained a-Ge, but there was also strong evidence for transformation of some of this phase to nanocrystalline dc-Ge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation